DNA: The Blueprint of Life and Its Journey to Discovery - Lekka, Marilia Lavinia (Open Schools Journal for Open Science, 2025)
This paper outlines the discovery of DNA as the carrier of genetic information, the foundational experiments that proved it, and the impact of this knowledge on modern science. It highlights key figures in the discovery—especially Rosalind Franklin—and discusses both the biological structure of DNA and its applications in medicine, genetics, and beyond.